Outcome after severe head injury treated by an integrated trauma system. - Coats, T J (1999)
OBJECTIVES: To describe outcome after treatment of severe head injury within an integrated trauma system. METHODS: A retrospective analysis of all patients with severe head injury admitted to the Royal London Hospital by the Helicopter Emergency Medical Service (HEMS) between 1991 and 1994. Type of injury was defined on initial computed tomography of the head and outcomes assessed 12 months after injury using the Glasgow outcome score. RESULTS: 6.5% of HEMS patients had long term severe disability (severe disability or persistent vegetative state on the outcome score); 34.5% made a good recovery. CONCLUSIONS: The concern that a large number of severely disabled long term survivors might result as a consequence of this system of trauma management is not confirmed. The case mix of severity of extracranial injuries in these patients makes comparison with other published series difficult, but these data fit the hypothesis that pre-hospital correction of hypoxia and hypotension after head injury improves outcome.